Studies on ductility of shear walls - Rao, G.V. Rama; Gopalakrishnan, N.; Jaya, K. P.; Dhaduk, Renish J. (Journal of Structural Engineering, 2025)
Ductile behaviour of shear wall is a prominent issue as the shear wall is a specially designed structural wall to resist earthquake forces. Ductility of shear wall is influenced by several factors like aspect ratio, axial load on shear wall, percentage of vertical reinforcement and percentage reinforcement in boundary element. A parametric study is carried out on the nonlinear ductile behaviour of shear wall using ABAQUS finite element software. Concrete Damaged Plasticity (CDP) model is used to represent the nonlinearity. The validity of the model is checked with the experimental results. The described procedure gives the direction and the necessary guidelines for the nonlinear analysis of shear walls. A comprehensive study is made on codal provisions for shear wall and suitable recommendations are made to improve the ductility of shear wall. From the parametric study, it is concluded that, to ensure ductile response under strong seismic shaking, the design of shear wall section needs to ensure the axial load to be not more than about 30% of the ultimate axial compression capacity.